The fate of job creation in the Philippines amid the automation revolution: A firm-level analysis - Raymond Gaspar; Nicholas Harris (Asian Development Bank Institute (ADBI), 2020)
Using the World Bank's Enterprise Survey for the Philippines, our analysis found that, on average, firms that deployed partial or full automation in their operations were more likely to hire more workers than fewer relative to their counterpart firms. These results suggest a net positive employment impact of automation, at least in the short run. The findings differ, however, by industries−net job creation is significant only among manufacturing firms. In contrast, we found that firms in the service industry have a higher likelihood of net job losses as they adopt partial or full automation. Indeed, there is an expectation that firms' decision to automate will cause labor market disruptions, which deserve immediate policy interventions. Human capital development, such as education and training, would be a critical policy lever to prevent the adverse effect of job displacement on the economic, social, and psychological well-being of individuals. The government should prepare workers to acquire the right set of skills and competencies, making them more flexible and able to fulfill new tasks amid further adoption of automation. Otherwise, the anxiety over the future loss of work will become a reality.
Keywords: J21; J23; J24; 330; automation; labor market disruptions; employment; Philippines